Circulating Free DNA in a Screening Program for Early Colorectal Cancer Detection. Issue 2 (March 2014) - Perrone, Federica; Lampis, Andrea; Bertan, Claudia; Verderio, Paolo; Ciniselli, Chiara M; Pizzamiglio, Sara; Frattini, Milo; Nucifora, Martina; Molinari, Francesca; Gallino, Gianfranco; Gariboldi, Manuela; Meroni, Emanuele; et al.
Aims and Background: The quantification and molecular characterization of circulating free DNA (cfDNA) have attracted much interest as new and promising, noninvasive means of detecting and monitoring the presence of surgical resectable colorectal cancer (CRC). Instead, the role of cfDNA in the early detection of malignant and premalignant colorectal lesions is still unclear. The aim of this study was to evaluate the predictive power of the quantification and KRAS status of cfDNA in detecting early colorectal lesions in plasma from healthy high-risk subjects. Methods: The study population consisted of 170 consecutive healthy high-risk subjects aged >50 years who participated in the screening program promoted by the Local Health Service (ASL-Milano) for early CRC detection and who underwent endoscopic examination after being found positive at fecal occult blood test (FOBT). Thirty-four participants had malignant lesions consisting of 12 adenocarcinomas (at an early stage in half of the cases) and 22 instances of high-grade intraepithelial neoplasia (HGIN) in adenomas; 73 participants had premalignant lesions (adenomas and hyperplasia), and 63 participants had no lesions. Plasma cfDNA was quantified by quantitative real-time PCR and analyzed for KRAS mutations by a mutant-enriched PCR. KRAS status was assessed also in matched adenocarcinoma and HGIN tissues. The distribution of cfDNA concentrations among FOBT-positive subjects with diagnosed lesion (cases) was compared with that of FOBT-positive subjects without lesions (controls) and its predictive capability (AUC) was assessed. Results: The predictive capability of cfDNA levels was satisfactory in predicting adenocarcinomas (AUC 0.709; 95% CI, 0.508–0.909) but not HGIN and premalignant lesions. The rate of KRAS mutations in plasma was low (5/170 = 3%) compared with the rate observed in the matched adenocarcinoma and HGIN tissues (45%). Conclusions: The use of cfDNA quantification to predict adenocarcinoma at an early stage in high-risk (aged >50 years and FOBT positive) subjects seems to be promising but needs more sensitive methods to improve cfDNA detection.